2016
DOI: 10.13189/ujer.2016.040531
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction Power of Servant and Ethical Leadership Behaviours of Administrators on Teachers' Job Satisfaction

Abstract: The purpose of this study is to identify servant leadership and ethical leadership behaviors of administrators and the prediction power of these behaviors on teachers'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…A negative relationship was found between all the dimensions of servant leadership and job satisfaction of teachers. However, ethical leadership had a positive relationship with teachers’ satisfaction, increasing with a higher level of ethical leadership, and decreasing with a higher level of servant leadership (Güngör, ). A positive and significant relationship was found between a transformational style and employees’ satisfaction, while a negative and significant relationship was shown between a transactional leadership style and job satisfaction among teachers’ at private universities in the UAE (Hijazi et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…A negative relationship was found between all the dimensions of servant leadership and job satisfaction of teachers. However, ethical leadership had a positive relationship with teachers’ satisfaction, increasing with a higher level of ethical leadership, and decreasing with a higher level of servant leadership (Güngör, ). A positive and significant relationship was found between a transformational style and employees’ satisfaction, while a negative and significant relationship was shown between a transactional leadership style and job satisfaction among teachers’ at private universities in the UAE (Hijazi et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…This definition outlines an essential part of ethical leadership. Güngör (2016) suggests that there is a new element in the notion of ethical leadership. According to him, one of the essences of ethical leadership is "service".…”
Section: Literature Review Ethical Leadershipmentioning
confidence: 99%
“…Three studies investigated the relationship between school principals' ethical leadership behaviours and job satisfaction (Çetin & Özcan, 2004;Güngör, 2016;Madenoğlu, Uysal, Sarıer, & Banoğlu, 2014). In two of these studies, Güngör (2016) and Madenoğlu, Uysal, Sarıer and Banoğlu (2014) indicated that ethical leadership could explain job satisfaction, and there were positive moderate correlations in-between. In the third study, Çetin and Özcan (2004) stated that ethical behaviours including tolerance, justice, honest, democracy and respect were positively and significantly related to teachers' job satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…The relationships with support and nature of the job are weaker compared to supervision. 25 Güngör (2016) Administrators' ethical leadership behaviours are positively and significantly related to teachers' job satisfaction ( r=.44, p< .01). Ethical leadership predicts teachers' job satisfaction (β= .30, p< .01).…”
Section: Appendix a Brief Findings Reported In The Studies Examinedmentioning
confidence: 99%